Tempering Proactive Cognitive Control by Transcranial Direct Current Stimulation of the Right (but Not the Left) Lateral Prefrontal Cortex - Gómez-Ariza, Carlos J.; Martín, María C.; Morales, Julia (Frontiers in Neuroscience, 2017)
Behavioral and neuroimaging data support the distinction of two different modes of cognitive control: proactive, which involves the active and sustained maintenance of task-relevant information to bias behavior in accordance with internal goals; and reactive, which entails the detection and resolution of interference at the time it occurs. Both control modes may be flexibly deployed depending on a variety of conditions (i.e., age, brain alterations, motivational factors, prior experience). Critically, and in line with specific predictions derived from the dual mechanisms of control account (Braver, 2012), findings from neuroimaging studies indicate that the same lateral prefrontal regions (i.e., left dorsolateral cortex and right inferior frontal junction) may implement different control modes on the basis of temporal dynamics of activity, which would be modulated in response to external or internal conditions. In the present study, we aimed to explore whether transcraneal direct current stimulation over either the left dorsolateral prefrontal cortex or the right inferior frontal junction would differentially modulate performance on the AX-CPT, a well-validated task that provides sensitive and reliable behavioral indices of proactive/reactive control. The study comprised six conditions of real stimulation [3 (site: left dorsolateral, right dorsolateral and right inferior frontal junction) × 2 (polarity: anodal and cathodal)], and one sham condition. The reference electrode was always placed extracephalically. Performance on the AX-CPT was assessed through two blocks of trials. The first block took place while stimulation was being delivered, whereas the second block was administered after stimulation completion. The results indicate that both offline cathodal stimulation of the right dorsolateral prefrontal cortex and online anodal stimulation of the right inferior frontal junction led participants to be much less proactive, with such a dissociation suggesting that both prefrontal regions differentially contribute to the adjustment of cognitive control modes. tDCS of the left-DLPFC failed to modulate cognitive control. These results partially support the predictions derived from the dual mechanisms of control account.